The characterization of tocols in different plants parts of six Japanese rice cultivars relating to their UVB-sensitivity - Nguyen Huynh Phuong, Uyen (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.